Sartre’s Critique of the Concept of Anthropological Structuralism in Strauss - Jeru, Mohammed Abdullah (International Journal of Psychosocial Rehabilitation, 2020)
Sartre goes in his critique of the structuralism, which sees the human being as a false formulation, because it overcomes the value of the structuralism and is absent from it after the effective practice from the historical person, as is evident in Sartre’s critique of structuralism, came different from his language and modest tone addressed it to the Marxists.